Comparing The Economy-wide Impact of Omnibus Law: An Input-Output Analysis - Tri Haryanto, Ari; P. Resosudarmo, Budy (Jurnal Ilmiah Administrasi Publik, 2021)
As the Indonesian government issued Omnibus Law to increase investment inflow to Indonesia, this paper tries to figure out investment in what sector that can generate the highest outcome in terms of the macro, micro, and environmental impacts, such that the Indonesian government should prioritize this sector as the investment targeted sector. Three sectors are considered: manufacturing, mining and quarrying, and electricity and gas. Using an I-O model and a microsimulation model, this paper examines the macro, micro, and environmental impacts of each investment scenario. The results reveal that in the short-run, investment in the electricity and gas sector generates the highest macro impacts, while investment in the mining and quarrying sector is better in reducing poverty and inequality, although it has a bigger environmental impact.